RNA Viruses: ROS-Mediated Cell Death. (8th May 2014) - Reshi, Mohammad Latif; Su, Yi-Che; Hong, Jiann-Ruey
Abstract : Reactive oxygen species (ROS) are well known for being both beneficial and deleterious. The main thrust of this review is to investigate the role of ROS in ribonucleic acid (RNA) virus pathogenesis. Much evidences has accumulated over the past decade, suggesting that patients infected with RNA viruses are under chronic oxidative stress. Changes to the body's antioxidant defense system, in relation to SOD, ascorbic acid, selenium, carotenoids, and glutathione, have been reported in various tissues of RNA-virus infected patients. This review focuses on RNA viruses and retroviruses, giving particular attention to the human influenza virus, Hepatitis c virus (HCV), human immunodeficiency virus (HIV), and the aquatic Betanodavirus. Oxidative stress via RNA virus infections can contribute to several aspects of viral disease pathogenesis including apoptosis, loss of immune function, viral replication, inflammatory response, and loss of body weight. We focus on how ROS production is correlated with host cell death. Moreover, ROS may play an important role as a signal molecule in the regulation of viral replication and organelle function, potentially providing new insights in the prevention and treatment of RNA viruses and retrovirus infections.